SINGLE PREMIUM FOR UNIT LINKED LIFE INSURANCE USING POINT TO POINT METHOD - Prima Dita, Yelly
Unit linked life insurance is one of the life insurance products providing the insured protection from death and to enjoy the benefit of investment such as stocks, bonds and mutual funds. In this research, the movement of the stock prices are assumed using Brownian motion. The method used to determine the amount of benefits for policyholders is point-to-point method which provides a guarantee when the stock prices extremely go down or go up. Moreover, this method is the simplest method because the stock prices only seen at the begin and end of the contract. There are many factors that in uence the unit linked benefits such as participation rates, rate of return, guarantee rates and cap rates. Unlike traditional life insurance which only calculates the risk of death. The advantages of unit linked life insurance compared to traditional life insurance can be seen from the amount of benefit because there is additional benefits from the investment return.